Design of enzyme-immobilized polymer brush-grafted magnetic nanoparticles for efficient nematicidal activity1. Issue 95 (15th October 2015) - Butt, A.; Farrukh, A.; Ghaffar, A.; Duran, H.; Oluz, Z.; ur Rehman, H.; Hussain, T.; Ahmad, R.; Tahir, A.; Yameen, B.
<x xml:space="preserve">Abstract</x> Parasitic nematodes adversely affect agricultural industry and global health. An efficient and reusable nematicidal platform is developed by immobilization enzyme on the surface of magnetic NPs.